HOMESCHOOLING: AN ALTERNATIVE TO NEW NORMAL ADAPTATION OF LEARNING - Eka Damayanti; Eva Meizara Puspita Dewi; Novita Maulidya Jalal; Nurfajriyanti Rasyid; Nurhaerani Haeba (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This research aims at finding out the public perception about the homeschooling which is chosen as an alternative in adaptation to the new normal learning. This research took forty-eight participants who are dominated by educators and magister or profession. Questionnaire as the instrument on this research was shared via google form. The collected data were analyzed by using descriptive statistics. The findings show that the participants think about the theme